2014
DOI: 10.1213/ane.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Rich Saline Improves Survival and Neurological Outcome After Cardiac Arrest and Cardiopulmonary Resuscitation in Rats

Abstract: Hydrogen-rich saline treatment improved survival and neurological outcome after cardiac arrest/resuscitation in rats, which was partially mediated by reducing oxidative stress, inflammation, and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…Moreover, in a CA/CPR swine model, increased pro-inflammatory cytokines expression, such as IL-1β and TNFα, were shown after resuscitation and played an important role in post-cardiac arrest syndrome [ 33 ]. Importantly, hydrogen-rich saline treatment could reduce the production of inflammatory cytokines, such as TNFα and IL-1β, after CA/CPR procedure so that it could improve survival condition and neurological outcome of rats [ 34 ]. Therefore, these studies indicated that reducing inflammation level might be a potential therapy to improve clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a CA/CPR swine model, increased pro-inflammatory cytokines expression, such as IL-1β and TNFα, were shown after resuscitation and played an important role in post-cardiac arrest syndrome [ 33 ]. Importantly, hydrogen-rich saline treatment could reduce the production of inflammatory cytokines, such as TNFα and IL-1β, after CA/CPR procedure so that it could improve survival condition and neurological outcome of rats [ 34 ]. Therefore, these studies indicated that reducing inflammation level might be a potential therapy to improve clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report emphasizes the critical role in SAH apoptosis due to the suppression of inflammatory responses through NF-κB and NLRP3 inflammasomes [300]. Additional benefits of hydrogen treatment have also been reported in animal models for other types of brain injury, such as those promoted by cardiac arrest and cardiopulmonary resuscitation [128], survival of retinal ganglion neurons after optic nerve crash [301] and neuroinflammation by sepsis [130].…”
Section: Hydrogen In Injuriesmentioning
confidence: 99%
“…Inhalation of hydrogen or using hydrogen-saline solutions has proven to be beneficial for brain damage produced by traumatic injury in rats [126] [127]. Hydrogen-rich saline solutions have been effective after rat brain ischemic damage produced by cardiac arrest or vascular causes [128] [129]. Finally, the protective effects of inhalation of hydrogen gas in mice have been also observed in damaged brains after inflammation [130].…”
Section: Hydrogen and Ischemia/reperfusion Injurymentioning
confidence: 99%
“…Cardiac arrest was induced by asphyxia. 18 Animals were anesthetized with pentobarbital (45 mg/kg) and the trachea was orally intubated with a 14-gauge plastic catheter. After tracheal intubation, polyethylene catheters (Becton Dickinson, Franklin Lakes, NJ, USA) were placed through the left femoral artery and vein into the abdominal aorta and the inferior vena cava, respectively.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%